Biochemical Effects to Toxicity of CCl4 on Rosy Barbs (Puntius conchonius) - Bhattacharya, H.; Lun, L.; Gomez R., G.D. (Our Nature, 2006)
Biochemical changes in the liver, kidneys and gills of rosy barbs due to toxicity of CCl4 were measured after 96 hour exposure. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), blood urea nitrogen (BUN) and creatinin (CRN), levels were measured. Significant increase in ALP, ALT, LDH and BUN activities were observed in the liver in the treated groups compared to controls (P < 0.05). AST level was significantly higher in the kidneys. This study indicates that the enzymatic activity was comparatively higher in the liver than kidneys or gills, suggesting that the liver is the target organ of CCL4 toxicity to rosy barbs. Keywords: Toxicity, Rosy Barb, CCl4 doi:10.3126/on.v3i1.330 Our Nature (2005)5:20-25